2012
DOI: 10.1590/s0034-737x2012000100013
|View full text |Cite
|
Sign up to set email alerts
|

Estimativas de parâmetros genéticos e correlações entre caracteres fenológicos e morfoagronômicos em feijão-caupi

Abstract: Estimates of genetic parameters and correlations between phenological and morphological traits in cowpeaDetermining the genetic variability and correlations between traits of interest for selection in a population is one of the stages in a breeding program. The objectives of this study was to evaluate the potential for genetic improvement of a population composed of 19 cowpea genotypes of erect and semi-erect growth habits, involving commercial varieties and advanced lines. Genetic and phenotypic parameters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
8
1
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 7 publications
7
8
1
15
Order By: Relevance
“…Therefore, indirect selection to increase the levels of these two nutrients by selection for NGP should be avoided. The magnitude and sign of the correlation between NGP and GY is consistent with results of Correa et al (2012), but in contrast to those of Silva and Neves (2011), who stated no correlation between these two traits.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, indirect selection to increase the levels of these two nutrients by selection for NGP should be avoided. The magnitude and sign of the correlation between NGP and GY is consistent with results of Correa et al (2012), but in contrast to those of Silva and Neves (2011), who stated no correlation between these two traits.…”
Section: Resultssupporting
confidence: 85%
“…A larger grain size and shorter maturation cycle of cultivars are among the current goals of cowpea breeding (Freire Filho et al 2011). This result contradicts Correa et al (2012), who found no correlation between these two traits in 20 cowpea genotypes.…”
Section: Resultscontrasting
confidence: 72%
“…Observou-se precisão de média a alta no controle ambiental uma vez que os coeficientes de variação experimental (CV e ) foram abaixo de 20% para todos os caracteres, variando de 1,64% para o caráter MAT a 16,58% para o caráter PROD (CRUZ et al, 2004 Benvindo et al (2010), Correa et al (2012). Este parâmetro fornece indícios do desempenho esperado de uma dada população na seleção de caracteres, o que permite inferir que a população em estudo é promissora para seleção dos caracteres supracitados.…”
Section: Resultsunclassified
“…Conhecer as correlações entre caracteres de interesse para a seleção permite ao melhorista conhecer o grau de associação entre caracteres de importância econômica, haja vista que a seleção sobre determinado caráter altera o comportamento do outro. As estimativas obtidas são usadas pelo melhorista para definir as estratégias adequadas para a obtenção de genótipos superiores baseadas nos caracteres mais importantes (CORREA et al, 2003).…”
Section: Introductionunclassified
“…A alta variabilidade genética associada com a cultura (Bertini et al 2009;Correa et al 2012), mesmo esta sendo exótica, pode ser compreendida quando se considera que as primeiras introduções no Brasil ocorreram há cerca de 460 anos, tempo suficiente para a existência de segregações e até mesmo mutações que foram disseminadas em sucessivos plantios, contribuindo para a alta variabilidade atual (Freire Filho et al 2011). No estado do Acre, onde o plantio do feijão-caupi é realizado há, pelo menos, cem anos (Martins e Costa 2009), esta cultura se transformou em importante fonte de renda e proteína para as populações tradicionais e agricultores familiares (Pereira et al 1997).…”
Section: Introductionunclassified